Delta‐like ligand 4 inhibitor drug treatment induces pulmonary hypertension in cancer clinical trials - Casandra E. Besse; Nolan M. Winicki; Cristian Puerta; Moises Hernandez; Jason X.‐J. Yuan; Patricia A. Thistlethwaite (Pulmonary Circulation)
Abstract Delta‐like ligand 4 (DLL‐4) inhibitor drugs are an emerging cancer treatment. In clinical trials for solid organ malignancies, intravenous administration of monoclonal antibodies that inhibit DLL‐4 is associated with development of pulmonary hypertension, in the absence of left ventricular dysfunction. Analysis of 13 clinical trials showed that pulmonary hypertension is a complication of DLL‐4 inhibition.